STUDI LIVING QUR’AN: ANALISIS TRANSMISI TEKS AL-QUR’AN DARI LISAN KE TULISAN - Turmuzi, Muhamad (Prodi Ilmu Al-Qur'an dan Tafsir, 2022)
This paper tries to explore the scope of the study of living quran and analyze the transmissions that occur in the al-Qur'an text from spoken to written. In general, many previous writings have provided research results related to the living Qur'an study. However, this paper comes with a focus on the process of transmitting the al-quran text from speech. There are at least three large groups of studies on the study of the Qur'an. First, research that places the Qur'an as the object of research. The second is research on the reading results of the Qur'anic text, both in the form of interpretive theories and in the form of exegetic thinking. The third is research that examines social responses or attitudes towards al-Qur'an or the results of reading al-Qur'an. The process of transmitting the Koran is marked by oral and written traditions that have existed since the time of the Prophet Muhammad. This tradition continued from the time of the Prophet to the time of the Caliph Uthman bin Affan, who was the peak of the historical chain of transmission of the Qur'an.